Das Gut des natürlichen Sterbens: Anmerkungen zu einer moraltheologischen Argumentationsfigur - Goertz, Stephan (Zeitschrift für evangelische Ethik, 2008)
Anyone approaching the ethical issue of Euthanasia from the perspective of moral theology will contribute a central role for its evaluation to the concept of "dying naturally". This principle of dying naturally, so it is argued from a normative point of view, shall never be substantially questioned or bent. In the present essay, this argumentation will be subjected to a thorough critique. Any arguments against Euthanasia never should fail to recognize the interactive context. Human dying in dignity normatively is linked clearly to the solidarity of all members of society.